A retrospective review: long-term outcomes and predictors affecting long-term outcomes in osteosarcoma patients in the Groote Schuur Hospital patient population - Hart, Heide (Division of Radiology, 2017)
Background: Predictive factors for long-term outcomes in osteosarcoma patients are still controversial. There is no literature available regarding these factors in a patient population in a developing country. Objectives: To determine the outcome of treatment of osteosarcoma patients treated at Groote Schuur Hospital from 1990-2012 in terms of local control (LRC), disease free survival (DFS) and overall survival (OS) and to determine the value of suggested predictive factors in this population. Patients and methods: Retrospective review of all patients diagnosed and treated with osteosarcoma at Groote Schuur Hospital between 1990 and 2012, considering OS, DFS and LC. This review assesses the significance of suggested predictive factors from other studies, namely, HIV status, age at diagnosis, site of primary disease, type of chemotherapy used, response to chemotherapy and type of surgery in terms of OS, DFS and LC. Results: Forty-three patients with histologically confirmed osteosarcoma were treated at Groote Schuur Hospital between 1990 and 2012. Median 5 year OS was 57.8%. On univariate analysis, the site of disease was the only statistically significant predictive factor for prognosis. Conclusion: On univariate analysis, patients with axial disease have a worse predicted prognosis than those with primary disease in their extremities. The long-term outcome in our local clinical setting correlates favourably with the available international data. Due to the limited number of patients in the review, further research into HIV status, age, type of chemotherapy, type of surgery and their predictive value for prognosis in our patients with osteosarcoma is warranted.